US Food Aid and Civil Conflict - Nunn, Nathan; Qian, Nancy (American Economic Review, 2014)
We study the effect of US food aid on conflict in recipient countries. Our analysis exploits time variation in food aid shipments due to changes in US wheat production and cross-sectional variation in a country's tendency to receive any US food aid. According to our estimates, an increase in US food aid increases the incidence and duration of civil conflicts, but has no robust effect on interstate conflicts or the onset of civil conflicts. We also provide suggestive evidence that the effects are most pronounced in countries with a recent history of civil conflict. (JEL D74, F35, O17, O19, Q11, Q18)